2014
DOI: 10.1163/15707563-00002446
|View full text |Cite
|
Sign up to set email alerts
|

The metapleural glands of fungus-growing and non-fungus-growing ants: Ultrastructural study

Abstract: The metapleural glands are considered an autapomorphic structure to ants and probable have an antibiotic or antifungal function. The present study was aimed at investigating the ultrastructural mor phology of the metapleural glands in ants which have different feeding types: from fungus-growing ants, the higher and lower attine, and non-fungus-growing ants from the tribes Blepharidattini and Ectatommini analyzed by transmission electron microscopy. Plasma membrane invaginations in secre tory cells of both fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Larger colonies may have more reliance on the MG [34], whereas T. curvispinosus colonies often containing under 100 workers. Previous research has also suggested more general importance of MG for fungal growing ant species, due to stronger pathogen pressure [43]. Perhaps removing MG gland function within a larger, fungal-growing species, would show stronger effects to social pathogen resistance.…”
Section: Discussionmentioning
confidence: 98%
“…Larger colonies may have more reliance on the MG [34], whereas T. curvispinosus colonies often containing under 100 workers. Previous research has also suggested more general importance of MG for fungal growing ant species, due to stronger pathogen pressure [43]. Perhaps removing MG gland function within a larger, fungal-growing species, would show stronger effects to social pathogen resistance.…”
Section: Discussionmentioning
confidence: 98%